Rancang Bangun Mesin Pengiris Talas Semir - Sugandi, Wahyu; Yusuf, Asep; Thoriq, Ahmad (Rekayasa Mesin, 2017)
Talas semir is a superior commodity in Sumedang. Talas semir can be made into various type of snacks such as chips. The best quality of Talas semir chips can be produced by using the best cutting machine. Based on some experimental results of the cutting machine for producing talas semir chips, the design of cutting machine was not ergonomic. The machine was uncomfortable to be operated. This study aims to designing and creating the ergonomic cutting machine for producing talas semir chips. This machine consists of cutter, operator seat, product holder, axis of cutter disk, electric motor and transmission systems including belt and pulley. Based on the experiment, the theoretical and actual machine capacity are 47 kg/jam and 38 kg/jam, respectively. Whereas, the efficiency of this machine is 81%. By using this machine, the best quality of talas semir chips is produced aproximately 80% and 530 watt power is required.